Immunity to Francisella - Cowley, Siobhan; Elkins, Karen (Frontiers in Microbiology, 2011)
In recent years, studies on the intracellular pathogen Francisella tularensis have greatly intensified, generating a wealth of new information on the interaction of this organism with the immune system. Here we review the basic elements of the innate and adaptive immune responses that contribute to protective immunity against Francisella species, with special emphasis on new data that has emerged in the last 5 years. Most studies have utilized the mouse model of infection, although there has been an expansion of work on human cells and other new animal models. In mice, basic immune parameters that operate in defense against other intracellular pathogen infections, such as IFN-gamma, TNF-alpha, and reactive nitrogen intermediates, are central for control of Francisella infection. However, new important immune mediators have been revealed, including IL-17A, TLR2, and the inflammasome. Further, a variety of cell types in addition to macrophages are now recognized to support Francisella growth, including epithelial cells and dendritic cells. CD4+ and CD8+ T cells are clearly important for control of primary infection and vaccine-induced protection, but new T cell subpopulations and the mechanisms employed by T cells are only beginning to be defined. A significant role for B cells and specific antibodies has been established, although their contribution varies greatly between bacterial strains of lower and higher virulence. Overall, recent data profile a pathogen that is adept at subverting host immune responses, but susceptible to many elements of the immune system’s antimicrobial arsenal.